ISLAM NUSANTARA PERSPEKTIF AHLUSSUNNAH WAL JAMA’AH: DIALEKTIKA AQIDAH, TRADISI, DAN KEBUDAYAAN LOKAL - Masnunah, Masnunah; Asfufah, Ismiati; Muyassaroh, Siti Rohmah; Saifuddin, Saifuddin (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2025)
Islam Nusantara is often understood as an expression of Islam that is accommodative to local culture, but studies that systematically place it within the theological framework of Ahlussunnah wal Jama’ah (Aswaja) are still relatively limited. This article aims to analyze Islam Nusantara from the perspective of Aswaja by emphasizing the dialectic between aqidah, tradition, and local culture in the Islamic practices of Indonesian society. This study uses a qualitative approach through conceptual analysis and literature review of relevant classical and contemporary sources. The results of the study show that Aswaja functions as a theological and methodological foundation that enables the integration of pure aqidah and acceptance of local traditions through the principles of tawassuth (moderation), tawazun (balance), i'tidal (justice), and tasamuh (tolerance). This synergy shapes the character of Islam Nusantara, which is contextual, inclusive, and adaptive to socio-cultural realities without obscuring the basic principles of Islamic teachings. This article emphasizes that Islam Nusantara based on Aswaja is not only relevant as a model of cultural da'wah, but also contributes significantly to building socio-religious coexistence and strengthening the discourse of moderate Islam in Indonesia's pluralistic society.